Mature Cystic Teratoma of Ovary with Abnormally High Levels of Ca19-9: A Case Report - Joana Sampaio; Inês Sarmento-Gonçalves; Joana Moreira Barros; Joana Felix; Pedro Tiago-Silva (Revista Brasileira de Ginecologia e Obstetrícia, 2016)
Abstract Mature cystic teratomas, or dermoid tumors, are the most common benign ovarian neoplasms in young women. Malignant transformation is rare, and occurs in less than 2% of the cases. The heterogeneous histological composition of these tumors may be responsible for the occasional elevation of various tumor markers, such as Ca19-9 and Ca125. We describe one case of mature cystic teratoma in a 50-year old woman with the second highest level of Ca19-9 (8922.76 UI/mL) described in the literature. We concluded that abnormal levels of Ca19-9 are not necessarily associated with ovarian malignancy, and may lead to unnecessary medical intervention and patient anxiety. Therefore, the clinical features, imaging studies and antigen testing should be interpreted carefully, and should not limit the surgical approach.